Application of Hormonal Preparations to Stimulate the Sexual Cycle and Increase Fertilization Rate in Cows - N.K. Tajieva; B.A. Jumanov; H.S. O‘rinov (American Journal of Biomedicine and Pharmacy, 2026)
Efficient reproduction management in dairy and beef cattle is a crucial factor determining the sustainability and profitability of livestock production. One of the major challenges in modern cattle breeding is the irregular manifestation of estrus and the difficulty in determining the optimal time for artificial insemination. Hormonal regulation of the reproductive cycle has become an effective biotechnological approach for synchronizing estrus and improving fertilization efficiency. This study analyzes the effectiveness of hormonal preparations used to stimulate the reproductive cycle and increase fertilization rates in cows and heifers. Special attention is given to the physiological mechanisms of prostaglandins, progesterone, and other biologically active substances in regulating ovarian activity and synchronizing estrus. The results of experimental and literature-based analysis indicate that the use of prostaglandin F2α and its synthetic analogues significantly improves reproductive management efficiency in cattle herds. Estrus synchronization protocols allow coordinated insemination and reduce labor costs associated with estrus detection. The fertilization rate after the first insemination using prostaglandin analogues reached 57.1%, which is comparable to natural fertilization rates. Additional hormonal combinations including estradiol and GnRH demonstrated improved control over ovulation timing. The study confirms that hormonal regulation of reproductive processes plays a key role in modern livestock biotechnology. Properly designed hormonal protocols contribute to increased reproductive efficiency, improved herd management, and enhanced productivity in cattle farming.